Influence of imidazole derivatives on the dielectric and energy storage performance of epoxy. (9th December 2021) - Luo, Jiaming; Zhang, Lei; Sun, Wenjie; Mao, Jiale; Zheng, Yiting; Wang, Shuang; Zhang, Ziqi; Chen, Yingxin; Cheng, Yonghong
Abstract: Imidazoles are widely used as curing agents and accelerators for fabricating crosslinked epoxy materials applied in electrical and electronic fields. However, the intrinsic chemical structure of imidazole derivatives would greatly influence the polymerisation process, and further change the electrical properties, which was not emphasised. To achieve an in‐depth understanding, commonly used imidazole only containing pyridine‐type nitrogen and imidazole with both pyridine and pyrrole‐type nitrogen were selected in this study. Electrical properties including dielectric properties, volume resistivity, breakdown strength, and especially energy storage performances were systematically investigated. We figured out that higher breakdown strength, glass transition temperature, and lower dielectric loss can be achieved with imidazole containing pyrrole‐type nitrogen. Structure‐induced curing mechanism diversity and the generated differences in polymer network were highlighted. With the capability to incorporate into the polymer network, the dielectric constant/loss of epoxy cured by imidazole containing pyrrole‐type nitrogen is less sensitive with variation in concentration and a high breakdown strength of 577.9 MV/m was achieved. On the contrary, conspicuous decrease in the breakdown strength and increase in dielectric loss of the epoxy cured by imidazole only containing pyridine‐type nitrogen were observed, especially at high concentration. Moreover, we also found that the epoxy can be fabricated into films with an attractive energy storage density/efficiency of 1.1 J/cm 3 /97%@200 MV/m, which is twice of the commercial dielectric polypropylene film under the same electric field.